Swedish opinion 1979-1985 - Boalt, Gunnar; Ekman, Gunnar; Hultgren, Sten; Stiftelsen för Opinionsanalyser (Stiftelsen för Opinionsanalyser, 1985)
Swedish Opinion 1979-1985 is a merged version of the recurring questions in the Swedish Opinion surveys. Questions asked in three or more of the surveys are included. These questions deals with: work and working conditions; trade unions; the importance of a number of changes in one´s own personal conditions; the importances of a number of political issues; political party with best ideas to achieve improvements in a number of fields; opinion on the political parties; important factors when deciding how to vote; reading frequencies for a number of daily papers, weeklies and magazines; political opinion of daily papers read; interest in the political debate in mass media; interest in a number of activities; values in life; improvements wanted in one´s own life; bank savings; opinion on the influence a number of organizations and groups have in society. Background variables include information on marital status, income, occupation, housing, education and place of residence.

Swedish Opinion 1979-1985 is a merged version of the recurring questions in the Swedish Opinion surveys. Questions asked in three or more of the surveys are included. These questions deals with: work and working conditions; trade unions; the importance of a number of changes in one´s own personal conditions; the importances of a number of political issues; political party with best ideas to achieve improvements in a number of fields; opinion on the political parties; important factors when deciding how to vote; reading frequencies for a number of daily papers, weeklies and magazines; political opinion of daily papers read; interest in the political debate in mass media; interest in a number of activities; values in life; improvements wanted in one´s own life; bank savings; opinion on the influence a number of organizations and groups have in society. Background variables include information on marital status, income, occupation, housing, education and place of residence.
Svensk opinion 1979-1985
SVOP79-85
Keywords: internal politics; inrikespolitik; Media; Media; Working conditions; Arbetsförhållanden; Political behaviour and attitudes; Politiska beteenden och attityder; Government, political systems and organisations; Regering, politiska system och organisationer; Social Sciences; Samhällsvetenskap